The role of modern means of proof in proving age of the marriage contract - Saad, Walaa; Hasan, Jaleel (Journal of Legal Sciences, 2022)
Scientific and technical developments have led to the development of new means of a new nature in the field of judicial proof, which have contributed to a large percentage in bringing judicial facts closer to reality, and sometimes beyond mere approximation to monitor the truth that may be absent from its person, as if this fact is scientific, and among these issues is a Proof of the age required for the marriage contract, which is one of the conditions that must be met for the marriage contract, which has raised problems for immigrants; the displaced; And for some individuals who belong to families that refuse to legally register them, and because marriage before puberty may cause some psychological problems that later lead to suicide as a means of salvation, or translating those problems with violence, we will show through this research the legislative position to determine the necessary age with a list of means Modern evidence that helps in this, by deriving it from some scientific studies, and clarifying the extent of certainty that it grants.